El Excentrico, 1961-03-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
March 5, 1961 [5 de marzo de 1961]. Ano 11, No 10. Cover has photograph of Ernie Vasquez receiving a "Outstanding Member of the Year" award from Robert Rodriquez at American G.I. Forum of Santa Clara County.